Pemahaman Pelaku Usaha Produk Roti dan Kue Terhadap Undang Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal di Kecamatan Pesanggrahan - Fathur Rachman; Risdianto; Azhar Taufik; Usman Alfarisi; Laila Yumna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to provide an understanding of halal products to bread and cake product business actors in Pesanggrahan District. This study uses a research method with a qualitative descriptive approach, namely a research method related to writing a topic of discussion by describing it, namely describing the understanding of business actors regarding Law Number 33 of 2014 concerning Halal Product Assurance and explaining the application of understanding of Halal Assurance to bread and cake product business actors in Pesanggrahan District, as well as analyzing the supporting and inhibiting factors in the understanding of business actors regarding Law Number 33 of 2014 concerning Halal Product Assurance. The results of this study found that there are still many bread and cake product business actors who do not understand Law Number 33 of 2014 concerning Halal Product Assurance and there are still some business actors who do not have Halal certificates. In this study, the author made efforts starting from socializing the implementation of halal certification to raise awareness of bread and cake product actors to implement halal certification. The awareness of business actors is seen in the increase in cognitive aspects that lead them to carry out halal certification. The supporting factors are in the form of adequate support and facilities in the implementation of halal certification. Meanwhile, inhibiting factors in the form of inadequate follow-up policies mean that the implementation of halal certification has not yet been carried out properly.